Queer(ed) pedagogies: a critical perspective - Bauer, Gero (Zeitschrift für Pädagogik und Theologie, 2020)
Current political controversies concerning progressive concepts of sex education in schools lead to an often openly aggressive dispute about the handling of identity concepts, understandings of gender, and knowledge in school and extracurricular contexts. In addition to general emancipatory concepts which emphasise diversity and tolerance, the discussion increasingly considers queer-theoretical interventions. This article outlines the axiological questions of a queer pedagogy, and offers insights into practices which might emerge as a result of such considerations. At the same time, it formulates theoretical questions of a queer pedagogy as they pertain to a more general theory of educational processes, and which concern not only the practice of teaching and learning, but also the formation of educational theory.